Placental passage of antiepileptic drugs at delivery and neonatal outcomes. (7th April 2017) - Bank, Anna M.; Stowe, Zachary N.; Newport, D. Jeffrey; Ritchie, James C.; Pennell, Page B.
Summary: Children of women treated with antiepileptic drugs (AEDs) are at increased risk of adverse outcomes detectable in the neonatal period, which may be associated with the amount of AEDs in the fetal circulation. Placental passage of AEDs can be measured by calculating the ratio of umbilical cord to maternal AED concentrations collected at delivery. The aims of this study were to determine the umbilical cord concentrations and umbilical‐to‐maternal ratios for AEDs, and whether higher cord concentrations are associated with increased risk of neonatal complications. AED cord and maternal blood concentrations from 70 mother–newborn dyads and neonatal complications were recorded. Logistic regressions were performed to determine the association between AED concentrations and complications. Mean umbilical‐to‐maternal ratios for total concentrations ranged from 0.79 for carbamazepine to 1.20 for valproic acid, and mean umbilical‐to‐maternal ratios for free concentrations ranged from 0.86 for valproic acid to 1.42 for carbamazepine, indicating complete placental passage. Neither umbilical cord concentrations nor umbilical‐to‐maternal ratios were associated with adverse neonatal outcomes. Additional investigations are warranted to delineate the relationship between quantified fetal AED exposure and neonatal complications.